Bruton’s Tyrosine Kinase and Its Isoforms in Cancer - Wang, Xianhui; Kokabee, Leila; Kokabee, Mostafa; Conklin, Douglas S. (Frontiers in Cell and Developmental Biology, 2021)
Bruton’s tyrosine kinase (BTK) is a cytoplasmic tyrosine kinase that plays a pivotal role in B cell development, maturation and signaling. BTK has been found to regulate cell proliferation, survival and migration in various B cell malignancies. Targeting BTK with recently developed BTK inhibitors has been approved by the FDA for the treatment of several hematological malignancies and has transformed the treatment of several B cell malignancies. The roles that BTK plays in B-cells have been appreciated for some time. Recent studies have established that BTK is expressed and plays pro-tumorigenic roles in several epithelial cancers. In this review, we focus on a novel isoform of the BTK protein, BTK-C, that is expressed in epithelial cancers. We review recent work on the expression, localization, function and signaling transduction of novel isoform of BTK-C in breast cancer and other solid tumors.